Pemanfaatan Konsumsi Seduhan Teh Hijau (Camellia Sinensis) Dalam Upaya Menurunkan Kadar Kolesterol Pada Lansia Di Kecamatan Sumber Cirebon - Hery Prambudi; Solikhah Solikhah; Pipin Supenah; Misika Alam; Rizal Ibrahim Aji; Nadia Azka (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
Green tea (Camellia sinensis) is a plant known by the public as a drink that is quite economical and easy to obtain. Green tea contains polyphenol compounds that can lower cholesterol levels in the blood. Excessive cholesterol (Hypercholesterolemia) is a very feared threat because it is one of the causes of coronary heart disease and stroke. High cholesterol has become a common disease for the elderly, the increase in the number of elderly people must be followed by an increase in the degree of well-being, one of which is in the health sector. The rise of lifestyle and the effects of unhealthy eating behaviors have an impact on increasing cholesterol levels. The purpose of this activity is to reduce the rate of hypercholesterolonemia in the elderly through the use of the consumption of green tea brew on cholesterol levels in the elderly in Sumber Cirebon District. The method in this activity is to conduct counseling, observer of respondents and experiments by giving green tea brew then followed by checking cholesterol levels. The result of this activity is that green tea is able to lower cholesterol levels. The conclusion is that the infusion of green can provide benefits for the community, especially the elderly, in improving health and reducing the risk of cardiovascular disease.